Antibacterial activity of polysaccharides extracted from the root of Premna serratifolia (Wind killer) - Ginthujah, V.; Jayapria, S.; Sivasinthujah, S; Tharmila, C.J.; Srithevi, S.; Thirtsha, G. (University of Sri Jayewardenepura, 2024)
Background: Emerging infectious diseases, especially skin infections pose significant threats to human health. Conventional antibiotics encounter challenges of antibiotic resistance and side effects, necessitating the screening of novel antibiotics. Various plant polysaccharides exhibit significant antimicrobial efficacy. Premna serratifolia is a vital traditional herbal plant in which the root is used for treating various diseases including skin diseases, diabetes and fever. Objective: To evaluate the antibacterial activity of polysaccharides extracted from the root of P. serratifolia. Methods: P. serratifolia root collected from the Government Herbal Garden and Siddha Central Dispensary in Jaffna, was subjected to shade drying, powdering, defatting with petroleum ether, oligosaccharides removal by 80% ethanol followed by polysaccharide extraction through hot water extraction. Deproteinization was done at pH 8-9 with CaCl2 and the mixture was freeze dried. Total sugar content was estimated using phenol-sulphuric acid method using glucose as the standard. Antibacterial activity of polysaccharides of P. serratifolia root was evaluated using agar well diffusion method against Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922), with ciprofloxacin as the standard. Data were analyzed using one-way ANOVA followed by Turkey’s test at 5% significance level. Results: Yield percentage and total sugar content of polysaccharides of P. serratifolia root was found to be 5.25% and 69.46% respectively. Mean values of inhibition zones of polysaccharides of P. serratifolia root against S. aureus and E. coli at 60 mg/mL were 30.67±0.58 mm and 30.33±0.58 mm respectively, whereas standard showed 40.33±0.58 mm and 37 mm at 0.5 mg/mL respectively. The inhibitory effects showed by standard and polysaccharides of P. serratifolia root differed significantly (P<0.05) while there was no significant difference noted between the bacterial isolates. Conclusions: Polysaccharides derived from P. serratifolia root has an antibacterial potential. Further studies are required to isolate the active polysaachide/s responsible for the observed antibacterial activity